Chronic airway disease in primary ciliary dyskinesia—spiced with geno–phenotype associations. Issue 1 (29th March 2022) - Nielsen, Kim G; Holgersen, Mathias G; Crowley, Suzanne; Marthin, June K
Abstract: Primary ciliary dyskinesia (PCD) can be defined as a multiorgan ciliopathy with a dominant element of chronic airway disease affecting the nose, sinuses, middle ear, and in particular, the lower airways. Although most patients with PCD are diagnosed during preschool years, it is obvious that the chronic lung disease starts its course already from birth. The many faces of the clinical picture change, as does lung function, structural lung damage, the burden of infection, and of treatment throughout life. A markedly severe neutrophil inflammation in the respiratory tract seems pervasive and is only to a minimal extent ameliorated by a treatment strategy, which is predominantly aimed at bacterial infections. An ever‐increasing understanding of the different aspects, their interrelationships, and possible different age courses conditioned by the underlying genotype is the focus of much attention. The future is likely to offer personalized medicine in the form of mRNA therapy, but to that end, it is of utmost importance that all patients with PCD be carefully characterized and given a genetic diagnosis. In this narrative review, we have concentrated on lower airways and summarized the current understanding of the chronic airway disease in this motile ciliopathy. In addition, we highlight the challenges, gaps, and opportunities in PCD lung disease research.